An Overview of Smart Cities in India using Technology and Sustainable Development of Society - Dhwani Jain; Divyanshu Goyal; Krati Sharma; Drashya Malot (International Journal of Urban Design and Development, 2025)
This paper examines India's "Smart Cities Mission," which aims to create sustainable and livable urban centers through innovative technology solutions. A smart city uses data from electronic devices and sensors to improve the efficiency of essential services, improve infrastructure, and manage urban areas better. This model represents progress in several key areas, including smart governance, smart economy, smart environment, smart living, smart people, and smart mobility. For a developing country like India, which wants to become a developed nation by 2047, building these cities is crucial. This study looks at the potential to transform Indian cities into smart, eco-friendly hubs. It focuses on the challenges and strategies necessary to meet the Sustainable Development Goals (SDGs) set by the United Nations, demonstrating how a forward-thinking, environmentally conscious society can enhance the quality of life for its citizens. Smart people, smart mobility, smart administration, smart economics, smart environment, and smart lifestyle are just a few of the areas where a smart city signifies progress. When combined, these elements support improved lifestyles, environmental preservation, innovation, and transparency. The creation of smart cities is both a need and an opportunity for a quickly rising nation like India, which hopes to achieve developed status by 2047. It is feasible to maintain economic growth, accommodate growing populations, and lessen the environmental constraints brought on by urbanization by transforming current urban centers into technologically sophisticated, ecologically friendly hubs. This kind of society is the need of an hour for the developing country of India. India aims to developed country by 2047, this paper explores the possibility of developing the cities of India into a smart city with the use of technology, the focus will be on eco-friendly society with the challenges to meet in the challenges for the Sustainable Development Goal provided by the United Nation.
Keywords: Smart Infrastructure; smart city; sustainable development; urban development